2011
DOI: 10.1007/s00270-011-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

British Society of Interventional Radiology: Biliary Drainage and Stenting Registry (BDSR)

Abstract: These figures provide an essential benchmark for both audit and patient information. Identifying areas of good practice and those that require improvement will ultimately result in better patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
66
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 19 publications
10
66
3
4
Order By: Relevance
“…13 In comparison, in the present study, significantly lower mortality and morbidity rates of 10.9% and 12.6%, respectively, were demonstrated. The recent BSIR audit also reported that haemorrhage, sepsis, and renal failure were the most common major complications associated with the highest mortality risk, which is more or less consistent with the present findings from this series of patients.…”
Section: Discussioncontrasting
confidence: 35%
See 3 more Smart Citations
“…13 In comparison, in the present study, significantly lower mortality and morbidity rates of 10.9% and 12.6%, respectively, were demonstrated. The recent BSIR audit also reported that haemorrhage, sepsis, and renal failure were the most common major complications associated with the highest mortality risk, which is more or less consistent with the present findings from this series of patients.…”
Section: Discussioncontrasting
confidence: 35%
“…In general, complications may be classified into major and minor (Electronic Supplementary Material, Appendix S3), with the major complications classified as those that require hospital admission for an outpatient procedure, or those that cause an increase in the level of care or necessitate a prolonged stay for hospitalised patients, or lead to permanent unplanned sequelae or death. 8,9,13,17 Conversely, minor complications may be classified as having no sequelae, necessitating minimal therapy, or short-stay hospital admission for observation. 8,9,13,17 Major complications, such as haemorrhage, renal failure, and septicaemia, can be minimised with optimum patient management in the pre-procedural period.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…An additional benefit of participation in registry studies is the ability to compare outcomes with regional and national benchmarks, allowing for more robust quality control and improved patient care. 12,13 IR as a primary medical specialty is now in a better position than ever to lead evidence-based clinical research, as evidenced by the implementation of clinical studies such as the PRESERVE (Predicting the Safety and Effectiveness of Inferior Vena Cava Filters) trial (NCT02381509), a joint collaboration between the Society of Interventional Radiology (SIR) and the Society for Vascular Surgery (SVS). These studies provide important information regarding the safety and efficacy of both developing and established treatment options and are invaluable for the practicing IR physician in the today's fast-paced world of medical technology and research.…”
Section: Discussionmentioning
confidence: 99%